EFISIENSI USAHATANI DENGAN PELAKSANAAN SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU PADI - Hutapea, Yanter (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
Integrated Crop Management Field School (ICM-FS) of Paddy do not bound by classrooms, serving as a non-formal education for farmers to increase their knowledge and skills, especially in recognizing the potential, the preparation of farm plans, and overcome the problem. This study aims to compare the efficiency of rice production due to the application of innovation, cost, rice production and farm income earned before and after implementation of the (ICM-FS) of Paddy and between participants and non-participant farmers (ICM-FS) of Paddy. The study was conducted during the rainy season 2010/2011 at Pagarsari village, Purwodadi district, Musi Rawas regency using before and after application of technology approach and with and without the application of technology. The results of this study showed that compared to non participants farmers, the participants of (ICM-FS) of Paddy have a stronger motivation to know the progress of innovation that proved they were more active than nonparticipant farmer at the meeting group and study on the pilot plots. Economic benefits obtained after following the (ICM-FS) of Paddy is decrease in the cost of producing dry grain harvest from Rp 1384.22/kg to Rp 1229.56/kg. Efficiency is also evidenced by the increasing value of R/C from 1.8 to 2.43 and MBCR value was 5.3. Compared with non-participant farmers in the same season, the participants farmer were more efficient than non-participants. The cost to produce dry grain harvest by participants farmer was Rp1.229.56/kg, while non participant was Rp 1364.18. Value of R/C was 2.44 for participan farmers, while non-participant was 2.20 with MBCR value was 3.97.